The Influence of the Project Based Learning (PjBL) Model on Student Learning Outcomes in Data Presentation Material for Class IV SDN 1 Pagar Air Aceh Besar - Rahmadani, Suci; Fauzi, Fauzi; Fitriani, Suci (Universitas Syiah Kuala, 2024)
In the mathematics learning process, there are still many students who do not understand the concept of data presentation, this difficulty causes student learning outcomes to be less than optimal. The formulation of the problem in this research is whether there is an influence of the Project Based Learning (PjBL) learning model on student learning outcomes in class IV data presentation material at SDN 1 Pagar Air Aceh Besar. This research aims to determine the effect of the Project Based Learning (PjBL) model on student learning outcomes in class IV data presentation material at SDN 1 Pagar Air Aceh Besar. The approach used in this research is quantitative. The type of research used is quasi experimental design research with the Nonequivalent Control Group Design type. This research was conducted at SDN 1 Pagar Air which is located on Jalan Banda Aceh Medan KM 6, Meunasah Krueng, Want Jaya District, Aceh Besar Regency, Aceh Province. The sampling technique used was a total census/sampling technique with a sample of all class IVA and IVB students with a total of 60 students. Data collection was carried out using tests consisting of a pretest and posttest. Analysis of research data using IBM SPSS STATISTIC Version 26 for Windows with the N-Gain test and independent sample test. The results of hypothesis testing obtained a significance value (2-tailed) of 0.000 0.05. So the conclusion of the results in decision making is Ha. accepted and H0 rejected. Thus, it can be concluded that there is a significant influence of the use of the Project Based Learning (PjBL) learning model on student learning outcomes in class IV data presentation material at SDN 1 Pagar Air Aceh Besar.